PROTOCOL: Measuring diet-related consumer behaviours relevant to low- and middle-income countries to advance food systems research: An evidence and gap map - Jager, Ilse de; Harrison, Megan; Wit, Renate F.; Sonneveld, Anne; Hesen, Rosil; Uyar, Betül T. M.; Verger, Eric O.; Ramos, Ana Islas; Vargas, Melissa; Wijesinha‐Bettoni, Ramani; Hachem, Fatima; Brouwer, Inge D. (Wiley, 2022)
This is the protocol for a evidence and gap map. The main objective of this evidence and gap map is to provide access to a systematic overview of available indicators for diet‐related consumer behaviours relevant to LMICs, to support policy makers and researchers to develop, monitor and revise food policies and programmes to leverage food systems transformations for healthier and more sustainable diets.